Electro-Optical Detection of Single Nanoparticles on a Nanopore-Optofluidic Chip. Issue 1720 (30th December 2014) - Fan, X.; Liu, L.; Park, E.; Schmidt, H.; Liu, Shuo; Zhao, Yue; Stott, Matthew; Parks, Joshua W.; Hawkins, Aaron R.; Schmidt, Holger
ABSTRACT A solid-state nanopore was integrated into an optofluidic sensor chip, liquid-core anti-resonant reflecting optical waveguide (ARROW). The solid-state nanopore worked as a smart gate, which simultaneously provided characteristic electrical signals and controlled the entry of single nanoparticles into the liquid-core channel. The subsequent fluorescence detection further identified the nanoparticles by providing optical signals within a specific wavelength range. In this work, correlated electrical and optical detection of single nanoparticles, H1N1 viruses, and Î»-DNA molecules was demonstrated. Different types of particles in a mixture were successfully discriminated. Moreover, the flow velocity in the liquid-core channel was extracted with the help of combined analysis of electrical and optical signals. Enhanced electrical sensitivity using a solid-state nanopore with a thin limiting aperture sculpted by SiO2 deposition was also shown.